Heat capacities and thermodynamic functions of neodymia and samaria doped ceria. (July 2021) - Neilsen, Grace; Rosen, Peter F.; Dickson, Matthew S.; Popovic, Marko; Schliesser, Jacob; Hansen, Lee D.; Navrotsky, Alexandra; Woodfield, Brian F.
Highlights: Heat capacity and thermodynamic properties of several Nd and/or Sm doped cerium oxides are presented. Heat capacity measurements show a Schottky anomaly due to paramagnetic dopant nuclei below 5 K. Fits of the Schottky anomalies were used to calculate the hyperfine field surrounding the paramagnetic dopant. Abstract: Doped ceria materials are ionic conductors currently under investigation for use in solid oxide fuel cells, catalysts, and other applications. We measured the heat capacity of several doped ceria samples from 1.8 K to 300 K to better understand their physical properties. The samples used in this study were either singly doped with Nd or Sm, or co-doped with both Nd and Sm. This work complements an earlier detailed study of their heats of formation and ionic conductivity. Here we provide the thermodynamic functions based on theoretical fits of our heat capacity measurements including C p, m °, Δ0 T S m °, Δ0 T H m °, and Φ m °. We also detected splitting of nuclear magnetic states, which appeared as an upturn in the heat capacity below 10 K. We observed this phenomenon in all samples and provide calculations of the local magnetic field causing the splitting.